Production Response and Digestive Enzymatic Activity of the Pacific White Shrimp Litopenaeus vannamei (Boone, 1931) Intensively Pregrown in Microbial Heterotrophic and Autotrophic-Based Systems - Manuel J. Becerra-Dórame; Marcel Martínez-Porchas; Luis R. Martínez-Córdova; Martha E. Rivas-Vega; José A. Lopez-Elias; Marco A. Porchas-Cornejo (The Scientific World Journal)
Shrimp postlarvae were reared into different microcosm systems without water exchange; a traditional system based on simple fertilization to improve microalgae concentration (control), an autotrophic system (AS) based on the promotion of biofloc and biofilm by the addition of fertilizer and artificial substrates and a heterotrophic system (HS) based on the promotion of heterotrophic bacteria by the addition of nitrogenous and carbonaceous sources and artificial substrates. Better growth performance and survival were registered in shrimp from the AS and HS compared to the control. Feed conversion ratios were below 0.7 for all treatments, but AS and HS were significantly lower than the control. Regarding digestive performance, no significant differences were observed for trypsin, amylase and lipase activities among AS and control shrimp; however, shrimp from HS showed a higher trypsin and amylase activities, suggesting a higher digestive activity caused by the presence of microbial bioflocs. The presence of biofilm and bioflocs composed by either autotrophic or heterotrophic organisms in combination with formulated feed improved the growth performance and survival of shrimp. Apparently, such combination fits the nutritional requirements of shrimp.